2023
DOI: 10.1002/ehf2.14532
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AHR by ITE improves cardiac remodelling and function in rats after myocardial infarction

Xiaoyan Lin,
Weiqiang Liu,
Yong Chu
et al.

Abstract: AimsLeft ventricular remodelling subsequent to myocardial infarction (MI) constitutes a pivotal underlying cause of heart failure. Intervention with the nontoxic endogenous aryl hydrocarbon receptor (AHR) agonist 2‐(1′H‐indole‐3′‐carbonyl)‐thiazole‐4‐carboxylic acid methyl ester (ITE) in the acute phase of MI has been shown to ameliorate cardiac function, but its role in the chronic phase remains obscured. This study explores the beneficial role of ITE in delaying the progression of heart failure in the chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…In addition, some studies have shown that downregulation of p70S6K can inhibit apoptosis (Oeing et al., 2021). ITE may down‐regulate the phosphorylation of AKT/P70S6K signaling pathway by activating AhR receptor, thereby reducing cardiomyocyte apoptosis (Lin et al., 2023). In combination with these studies, AE‐411/41415610 may have a role in the AKT‐p70S6K pathway in apoptosis, but this requires further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that downregulation of p70S6K can inhibit apoptosis (Oeing et al., 2021). ITE may down‐regulate the phosphorylation of AKT/P70S6K signaling pathway by activating AhR receptor, thereby reducing cardiomyocyte apoptosis (Lin et al., 2023). In combination with these studies, AE‐411/41415610 may have a role in the AKT‐p70S6K pathway in apoptosis, but this requires further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MI, excessive remodeling of myocardial fibers can initiate a chain of events leading to myocardial fibrosis and heart failure (Zhang et al 2023 ). Current clinical use of drugs, such as angiotensin-converting enzyme (ACE) inhibitors, beta-blockers, and aldosterone antagonists, is hampered by side effects, such as hypotension and bradycardia (Lin et al 2023 ). Therefore, there is an urgent need to study the potential mechanism of myocardial fibrosis after MI and to identify new pharmacological targets to intervene in or delay the process of cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive production of reactive oxygen species further exacerbates cardiomyocyte damage and apoptosis. The AHR agonist ITE mitigates cardiomyocyte apoptosis by activating the Akt/p70S6K signaling pathway, thereby attenuating left ventricular remodeling and improving cardiac dysfunction following myocardial infarction (Lin et al 2023 ). Our findings demonstrate that NaW enhances glucose uptake by cardiomyocytes and activates the pentose phosphate pathway (PPP) for NADPH production (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%